2002
DOI: 10.1002/mrdd.10035
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of the epilepsies in children

Abstract: The epilepsies are a heterogeneous collection of neurological conditions and syndromes characterized by recurrent, unprovoked, paroxysmal seizure activity. There are several types of epileptic seizures and syndromes that are unique to children, including infantile spasms, Lennox-Gastaut syndrome and absence seizures. Febrile seizures and neonatal seizures, while not epilepsy, are relatively common types of seizures in infants and children and are likely markers of risk of later epilepsy. Thus, it is important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
160
1
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(183 citation statements)
references
References 88 publications
7
160
1
15
Order By: Relevance
“…It is unclear whether the absence seizures are primarily linked to the KCNJ11 gene mutation and represent an intermediate neurological phenotype between intermediate and full DEND syndrome. The multiple foci differ from the bilateral synchronous 3 Hz spike waves commonly seen in absence epilepsy with a genetic origin [23]. An alternative explanation is that it may be attributed to minor lesions of the brain originating from recurrent hypoglycaemia during early phases of life.…”
Section: Discussionmentioning
confidence: 83%
“…It is unclear whether the absence seizures are primarily linked to the KCNJ11 gene mutation and represent an intermediate neurological phenotype between intermediate and full DEND syndrome. The multiple foci differ from the bilateral synchronous 3 Hz spike waves commonly seen in absence epilepsy with a genetic origin [23]. An alternative explanation is that it may be attributed to minor lesions of the brain originating from recurrent hypoglycaemia during early phases of life.…”
Section: Discussionmentioning
confidence: 83%
“…The causes of epilepsy can be broadly categorised as structural abnormalities, metabolic disturbances and genetic factors. However, these causes account for only 25-45% of all cases, and there is no clear underlying cause in the remaining population, thus representing forms of idiopathic epilepsy [9].…”
mentioning
confidence: 99%
“…This leads to development of seizures from a particular area of the brain, called as "seizure focus". [2][3][4][5] Recent studies have revealed clinically relevant mechanisms of generalized and localized seizures, among which are inherited abnormalities of ion channels, hippocampal sclerosis, cortical malformations, and dysfunction of glial cells.…”
Section: Introductionmentioning
confidence: 99%